Power play: the use of space to control and signify power in the workplace. Issue 4 (3rd July 2020) - Hughes, Heidi; Hockey, John; Berry, Greg
ABSTRACT: The findings of this article emerge from an eight-month study examining career identity practices amongst a select group of fitness professionals in the U.K. We examine how the inter-relationship between physical and social space can denote how power is acquired, displayed, and used by individuals interacting in a shared space. The findings show that power is signified through spatial practices as individuals negotiate through triadic space, creating an identity of space and place for both trainer and client that identifies power, and signifies who has power. Fitness professionals with high levels of symbolic power are able to subvert organizational spatial norms to better serve themselves and their clients, while those with lower levels of symbolic power are forced to, or choose to, negotiate or abdicate space to others. These findings are relevant to a wide range of occupations where self-employment and contract workers interact in shared space.